2006
DOI: 10.1523/jneurosci.0223-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence fromIn VivoImaging That Synaptogenesis Guides the Growth and Branching of Axonal Arbors by Two Distinct Mechanisms

Abstract: To explore the relationship between axon arbor growth and synaptogenesis, developing retinal ganglion cell (RGC) axon arbors in zebrafish optic tectum were imaged in vivo at high temporal and spatial resolution using two-photon microscopy. Individual RGC axons were dually labeled by expression of a cytosolic red fluorescent protein (DsRed Express) to mark arbor structure and a fusion of the synaptic vesicle protein synaptophysin with green fluorescent protein (Syp:GFP) to mark presynaptic vesicles. Analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
319
2
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(349 citation statements)
references
References 45 publications
26
319
2
2
Order By: Relevance
“…6A-D), but the small size of axonal mitochondria precluded quantitative analysis of mitochondrial distribution and dynamics at the light microscopy level. We did not see any overt defects in the localization of the synaptic vesicle protein marker, synaptophysin:GFP (Meyer and Smith, 2006) in kbp st23 mutant axons (Fig. 6E,F).…”
Section: Research Articlementioning
confidence: 78%
See 1 more Smart Citation
“…6A-D), but the small size of axonal mitochondria precluded quantitative analysis of mitochondrial distribution and dynamics at the light microscopy level. We did not see any overt defects in the localization of the synaptic vesicle protein marker, synaptophysin:GFP (Meyer and Smith, 2006) in kbp st23 mutant axons (Fig. 6E,F).…”
Section: Research Articlementioning
confidence: 78%
“…To co-label axons and synaptophysin, embryos were injected at the one cell stage with 25 pg of syn:GFP-DSR plasmid DNA (Meyer and Smith, 2006). Embryos were screened at 96 hpf and those with suitably labeled neurons were imaged.…”
Section: Axonal Mitochondrial and Synaptic Vesicle Protein Labelingmentioning
confidence: 99%
“…Numerous studies have revealed developmentally regulated synaptic maturation during periods when the expression of LTP is also robust (Crair and Malenka, 1995;Rumpel et al, 1998;Chen and Regehr, 2000), and this synaptic maturation is correlated with axon remodeling during map refinement (Meyer and Smith, 2006;Ruthazer et al, 2006). Whether the experimentally induced LTP is physiologically relevant to circuit formation is unclear, however, because of the wide variety of induction protocols used and the lack of information about natural activity patterns during development.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, chronic NMDAR blockade serves to increase RGC arbor branch dynamics, suggesting that NMDAR activity and synaptic maturation normally stabilizes retinotectal projections during circuit formation (Rajan et al, 1999). Recent in vivo imaging of zebrafish and tadpole retinotectal axons reveals that synapse formation and maturation are tightly correlated with branch dynamics and may play an instructive role in arbor remodeling during map formation (Meyer and Smith, 2006;Ruthazer et al, 2006). Indeed, correlated activity is known to regulate RGC axon branch dynamics during development (Ruthazer et al, 2003;Hua et al, 2005), offering additional evidence that the refinement of retinotopic projections proceeds through activitydependent instruction and synaptic competition.…”
Section: Model Of Synaptic-competition-based Retinotopic Map Refinementmentioning
confidence: 99%
“…Thus, TPM allows imaging of thick biological specimens such as brain slices, intact embryos, and brains up to ϳ800 m deep into the tissues. 25,26 Rather than reviewing the extensive field of structural synaptic plasticity on which there are many excellent imaging studies and reviews, 3,18,23,[27][28][29] in this paper we will mainly focus on recent findings obtained by TPM in living mice that relate to structural changes of synapses in the normal and degenerating brain. Because live imaging of synapses is a relatively new field, there is still no consensus regarding the degree of synaptic dynamism at baseline and in response to experience.…”
Section: Introductionmentioning
confidence: 99%